Rancang Bangun Sistem Informasi Penjualan Pada Gading Murni Putra - Dhyaksa, Gilang Wira; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract :Â Gading Murni Putra is one of the companies that have major business in sector of stationery and office/school supplies and printing. During this time, Gading Murni Putra has only one information system that record all direct and online (email, livechat, by phone) transaction, so the transaction data is mixed together. Additionally, transaction that occur every day just recorded and not processed into a usefull information for decision making.Based on those problem, sales information system was created. This system has several process. Process for receiving sales order, sales transaction, and receipt of goods. For sales order and sales transaction process, it has each transaction for direct and online (email, livechat, by phone) transaction.This information system can generate report for most or least item sold, most profitable item, customer history report and customer mapping report. Report for most or least item sold and most profitable item can be separated by type of transaction, direct or online (email, livechat, by phone). This information system can be used by manager to evaluate sales transaction for each direct and online (email, livechat, by phone) transaction, in addition it can also be used by manager to knowing the information about customer.